Dietary effect of Galega orientalis Lam. flavonoid extract on broilers’ growth performance, antioxidant capacity, immune function, and bone metabolism - Nana I. Tchana; Huiyan Zhang; Yinchuan Pan; Shiyi Wang; Dieudonné M. Dansou; Xiaoxuan Xia; Qingyu Zhao; Chaohua Tang; Junmin Zhang (Poultry Science)
This study aimed to evaluate the impact of dietary Galega orientalis Lam. flavonoid extract (GOLFE) on production performance, biological markers, and bone health of white-feather broilers. A total of 540 one-day-old Cobb broilers were randomly assigned to six dietary groups: a negative control group (without additives; G0), four nutritional additive groups supplemented with GOLFE (G1:200 mg, G2: 400 mg, G3:800 mg, and G4:1600 mg), and a positive control group (supplemented with chlortetracycline; G5:100 mg). Each group consisted of 90 birds (6 replicates with 15 birds each) and the feeding trial lasted 42 days. Growth performance and blood profiles were assessed during two phases (days 1–21 and 22–42), while bone health, serum biochemical, antioxidant, and immune parameters were evaluated in the second phase (22–42 days). The results demonstrated that GOLFE supplementation significantly reduced mortality in birds, improved feed conversion ratio, and reduced feed intake (P < 0.05) without significant effect on body weight (P > 0.05). GOLFE also led to a reduction in white blood cell counts (P < 0.05). Serum biochemical and antioxidant analyses revealed substantial improvements in calcium (Ca) and phosphorus (P) concentrations (P < 0.05), alongside a decrease in MDA biomarkers, with an increase in SOD, CAT, and TAOC content (P < 0.05). Significant decrease of pro-inflammatory cytokines (P < 0.05), including interleukins (IL): IL-1β, IL-2, IL-4, IL-6, and IL-8 were also noticed. Additionally, growth plate histomorphometry indicated that GOLFE enhanced the microstructure of bone tissue, and tibia bone characteristics such as weight, length, strength (P < 0.05), and mineral content (Ca and P), (P < 0.05) were also improved. These findings suggest that GOLFE supplementation may promote better growth performance and overall health in broilers, positioning it as a potential natural alternative to antibiotics in poultry production.